Improved operation of simulated moving bed processes through cyclic modulation of feed flow and feed concentration - Schramm, Henning; Kienle, Achim; Kaspereit, Malte; Seidel-Morgenstern, Andreas (Chemical Engineering Science, 2003)
Recently, different strategies for improving simulated moving bed (SMB) chromatographic separation processes have been proposed, including a modulation of the feed flow (PREP, 15th International Symposium, Exhibit & Workshops on Preparative/Process Chromatography Ion Exchange, Adsorption/Desorption Processes & Related Separation Techniques, Lecture 201, Washington, DC, USA, pp. 53-54.) and the feed concentration (Chemical Engineering Technology 25(12) 1151) during the tacts. In this contribution these two different strategies are applied to a benchmark problem and are compared with each other. Physical explanations of the improvements obtained compared with the conventional operation mode are given in terms of moving concentration fronts. Practical aspects for the implementation of the different strategies are also discussed. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Feed concentration; Feed flow; ModiCon; Periodic operation; PowerFeed; Simulated moving bed chromatography